Policies and institutional and legal frameworks in the expansion of Brazilian biofuels - Andrade, R.M.T.; Miccolis, Andrew (Center for International Forestry Research, 2011)
This paper maps out and analyses the wide range of policies and players that have shaped the phenomenal rise of biofuels in Brazil, drawing comparisons between the ethanol and biodiesel industries. The sugarcane-ethanol sector’s expansion has been characterised by distinct waves of regulation and deregulation, heavy private investment and public financing for infrastructure, research and development. Close links with energy and climate change–related policies, the dualfuel car revolution, liberal foreign direct investment policies and fiscal and financial incentives have also played important roles. Questions are being raised about human rights and environmental justice due to poor working conditions, land concentration and displacement of smallholders as well as environmental impacts, especially in South-Central and Northeastern Brazil. The sugarcane-ethanol industry has sought to address these claims through voluntary governance and certification mechanisms. The Brazilian Government has also taken decisive action to forbid sugarcane expansion into sensitive ecosystems. Recent biodiesel feedstock policies aimed at smallholders have delivered substantial savings (US$1 billion/year) by substituting diesel imports, and made progress towards ‘social inclusion’. But these programs have fallen short of targets, as the prevailing feedstock is still soybeans followed by beef tallow, with production and processing still concentrated in the hands of large-scale soybean farmers and cattle ranchers. Despite robust and well-intended environmental, rural development and fiscal policies to support smallholders, some policies are extremely difficult to enforce given structural constraints faced by smallholders and the lack of adequate governance mechanisms.